A prospective study of serum metabolomic and lipidomic changes in myopic children and adolescents. (October 2020) - Du, Bei; Jin, Nan; Zhu, Xiurui; Lu, Daqian; Jin, Chengcheng; Li, Zhen; Han, Chunle; Zhang, Yani; Lai, Donghai; Liu, Kang; Wei, Ruihua
Abstract: Background: Myopia is a prevalent eye disorder, especially among children and adolescents in eastern Asian countries. Multiple measures have already been taken to prevent and treat myopia, including atropine and dopamine. However, the serum metabolic picture of myopia has not yet been studied as a whole and remains largely unclear. In this paper, a prospective and panoramic study was carried out to find out the whole serum metabolomic and lipidomic picture of myopia. Methods: With untargeted mass spectrometry (MS), myopia among 211 children and adolescents was studied. The MS features were first grouped across the samples. Then, compound annotation was carried out based on these features. Finally, the metabolite features were mapped to pathways, whose biological functions in myopia were studied and discussed. Results: A total of 275 metabolite features were derived from 92 aligned MS peak groups with significant fold changes, and then mapped to 33 pathways. By a comprehensive consideration of significance, fold change, importance score and appearance in different omics, 9 pathways were selected, and their biological functions were further analyzed. Among these selected pathways, 5 pathways were related with oxidative stress, a validated phenomenon during myopia development, while 5 pathways were related with dopamine receptor D2, whose molecular function in myopia treatment is not fully understood. A total of 177 metabolite features from 45 peak groups were related with the studied pathways. Conclusion: This prospective study shed light on the whole picture of metabolomic mechanism underlying myopia and provided guidance to further elucidation of compounds and pathways in this whole picture. Highlights: Serological metabolic/lipid changes discovered in myopic children and adolescents. Untargeted mass spectrometry revealed changes in 275 features and 33 pathways. Enriched pathways related with oxidative stress and dopamine receptor D2.